Chukchi Sea oil & gas lease sale 126 : draft environmental impact statement. - United States. Minerals Management Service. Alaska OCS Region. ([Anchorage, Alaska?] : U.S. Dept. of the Interior, Minerals Management Service, Alaska OCS Region, 1990)
"OCS EIS/EA MMS 90-0035." Includes index (v. 2). "July 1990." Shipping list no.: 90-494-P (v. 2). Shipping list no.: 90-497-P (v. 1). At head of title: Alaska outer continental shelf. Includes bibliographical references (v. 2, bibliography, p. 1-33). Mode of access: Internet.